2020
DOI: 10.1186/s12906-020-2864-2
|View full text |Cite
|
Sign up to set email alerts
|

Soyasaponins reduce inflammation by downregulating MyD88 expression and suppressing the recruitments of TLR4 and MyD88 into lipid rafts

Abstract: Background: Previous studies indicate that soyasaponins may reduce inflammation via modulating toll-like receptor 4 (TLR4)/myeloid differentiation factor 88 (MyD88) signaling. However, its underlying mechanisms are still not fully understood. Methods: Lipopolysaccharide (LPS)-challenged inflamed male ICR mice were intervened by intragastrical administration with 10 and 20 μmol/kg•BW of soyasaponin A 1 , A 2 or I for 8 weeks. The serum inflammatory markers were determined by commercial kits and the expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 40 publications
(116 reference statements)
3
16
0
Order By: Relevance
“…Both SS-A 2 and OCA significantly decreased the serum ALT level and liver cytokines expression, and medium and high dosage of SS-A 2 also reduced the serum TNF-level in the MCD diet-fed mice. These results are consistent with our previous studies supporting that SS-A 2 had hepatoprotective [35] and anti-inflammatory [35,37,53,50,54] bioactivities. Other types of soyasaponins were also shown to have hepatoprotective and anti-inflammatory bioactivities.…”
Section: Discussionsupporting
confidence: 94%
“…Both SS-A 2 and OCA significantly decreased the serum ALT level and liver cytokines expression, and medium and high dosage of SS-A 2 also reduced the serum TNF-level in the MCD diet-fed mice. These results are consistent with our previous studies supporting that SS-A 2 had hepatoprotective [35] and anti-inflammatory [35,37,53,50,54] bioactivities. Other types of soyasaponins were also shown to have hepatoprotective and anti-inflammatory bioactivities.…”
Section: Discussionsupporting
confidence: 94%
“…We proposed that OVT might play an immunomodulatory role through the MyD88 signaling pathway mediated by TLR4. Our results were similar to previous research results of wheat germ globulin (Wu et al., 2017 ) and soyasaponins (Chen et al., 2020 ).…”
Section: Discussionsupporting
confidence: 93%
“…Lactoferrin suppresses LPS-induced expression of NF-кB pathway in RAW264.7 cells through TLR4 (Nemati et al, 2020) results of wheat germ globulin (Wu et al, 2017) and soyasaponins (Chen et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The dysregulation of lipid rafts played a key role in the pathogenesis of inflammatory, infectious diseases and cancer. One study demonstrated that LPS stimulated macrophage inflammation by encouraging the recruitment of TLR4 and MyD88 into lipid raft ( Chen et al, 2020 ). Our study demonstrated that nicotine induced the activation of NLRP3 inflammasome in macrophage by prompting the recruitment of α1-nAchR in lipid raft.…”
Section: Discussionmentioning
confidence: 99%